2018
DOI: 10.1039/c8ra03282c
|View full text |Cite
|
Sign up to set email alerts
|

Spitzer shaped ZnO nanostructures for enhancement of field electron emission behaviors

Abstract: We observed enhanced field emission (FE) behavior for spitzer shaped ZnO nanowires synthesized via a hydrothermal approach. The spitzer shaped and pointed tipped 1D ZnO nanowires of average diameter 120 nm and length $5-6 mm were randomly grown over an ITO coated glass substrate. The turn-on field (E on ) of 1.56 V mm À1 required to draw a current density of 10 mA cm À2 from these spitzer shaped ZnO nanowires is significantly lower than that of pristine and doped ZnO nanostructures, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In the beginning, the pristine ZnO nanowires (≡ ZnO/ITO) were subjected to electron FE at the separation of 1500, 2000 and 2500 μm. More details on these field emission measurements are available elsewhere . Owing to the higher current density observed for pristine ZnO nanowires at the separation of 2000 μm, the FE studies of Au@ZnO nanowires (≡ Au/ZnO/ITO) were performed at the anode‐cathode separation of 2000 μm.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In the beginning, the pristine ZnO nanowires (≡ ZnO/ITO) were subjected to electron FE at the separation of 1500, 2000 and 2500 μm. More details on these field emission measurements are available elsewhere . Owing to the higher current density observed for pristine ZnO nanowires at the separation of 2000 μm, the FE studies of Au@ZnO nanowires (≡ Au/ZnO/ITO) were performed at the anode‐cathode separation of 2000 μm.…”
Section: Resultsmentioning
confidence: 65%
“…The UPS spectra recorded at an energy of 23 eV for Au decorated ZnO nanowires shown in Figure , is utilized to calculate the work functions. There are obvious changes in the shape of valence band spectra for Au@ ZnO emitters compare to that of ZnO emitters . Two distinct peaks are observed in the VBS of Au@ZnO nanowires, where lower and higher binding energy peaks are assigned to the nonbonding O(2p) orbitals and hybridization of the O(2p) and Zn(4 s) orbitals, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The XPS analysis (not provided here) is very much akin to that in our studies reported earlier. 15 The phase purity and crystal structure of the as-synthesised ZnO nanowires analyzed from X-ray diffraction (XRD) studies (ESI †) confirmed the growth of hexagonal wurtzite ZnO nanowires without any defects or impurity phases. Therefore, the present hexagonal ZnO nanowires with a high degree of crystallinity were expected to enable better sensing response for hazardous and toxic gases such as CO, C 2 H 5 OH, NH 3 , etc.…”
Section: Resultsmentioning
confidence: 84%
“…The surface morphological appearance of the hexagonal ZnO nanowires is detailed elsewhere. 15 The highly porous thin film of single-crystalline ZnO nanowires is expected to provide distinct gas sensing properties. The energy dispersive X-ray (EDX) spectra of the ZnO nanowires (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation